(untitled) (Homoeopathy for All, 2023)
Irritable bowel syndrome (IBS) is a functional bowel disorder characterized by abdominal pain or discomfort and altered bowel habits in the absence of detectable structural abnormalities. It is diagnosed by using clinical criteria. Depending on the diagnostic criteria employed, IBS affects around 11% of the population globally. There is a female predominance in the prevalence of IBS, 25% less IBS diagnosed in those over 50 years and no association between IBS and socioeconomic status.